The Struggle for Land in Morocco: A Case Study of Amazigh - Banane, Mohamed Cheikh; Ezzerouali, Souad; Elzein, Ahmed Mohamed (Fakultas Syariah UINSI Samarinda, 2024)
This paper addresses the issue of the conflict over land between the state and tribes in the Great Souss plain in Morocco. The focus of this study is on the Amazigh tribes. It explores the motives that contributed to the emergence of tribal protests, particularly their demands for land rights, following the civil reforms promised by the Arab Spring in 2011. Through a direct examination of the growing dissatisfaction among these communities, the study reveals that the political failure to democratize society, characterized by consistent confusion at the level of governmental and institutional frameworks and the law's failure to regulate spatial justice on the ground, have both played a role. This situation has prompted tribes, feeling a sense of historical oppression, to claim their rights to the land that the state has increasingly opened up for investment without considering the traditional rights of these indigenous groups.